A framework for identifying early writing development. (2nd July 2022) - Kabel, Kristine; Bremholm, Jesper; Bundsgaard, Jeppe
Abstract : In this article, we present a novel framework for identifying young students' writing development in the first years of primary school (age 6–8 years). It was developed to analyse a large number of student texts (n = 803), all in the format of digitised books, as part of the large-scale Danish research project titled Teaching Platform for Developing and Automatically Tracking Early Stage Literacy Skills (ATEL, 2018–2023). In this project, based on a text-oriented model of writing, we aim to gain insights into less considered dimensions of emergent writing. Specifically, we consider how young students construct sentences and expand their meaning-making repertoires in this regard, as well as how they tie a whole text together and begin to express interpersonal meaning. In developing the framework, we took inspiration from both formal and functional linguistic approaches to young students' writing development and constructed a comprehensive framework to examine the first steps into ways of communicating through writing in school. Furthermore, through a theory-and data-driven process, we developed the framework to suit emergent writing in the educational and language context in Denmark. In addition to presenting the framework in this article, we discuss its limitations and potentials for research and practice.